Permainan Uno Stacko dalam Keterampilan Berbicara Bahasa Jerman - Mardiana Mardiana; Laelah Azizah (Universitas Negeri Makassar, 2023)
Abstract. This study aims to know the planning, implementation, and results of applying the Uno Stacko game in the speaking skills the students of SMA Negeri 1 Gowa. The research data consists of two types data, namely qualitative and quantitative. Qualitative data were obtained through observation and analyzed using descriptive methods. Quantitative data were obtained from the results of German speaking skill tests and were analyzed using percentage techniques. The results obtained in the first cycle reached 50,2% and in the second cycle reached 78%. This means that the Uno Stacko game can improve the German speaking skills of SMA Negeri 1 Gowa students.Keyword: Uno Stacko, speaking skill, German language.